2022
DOI: 10.1021/acsnano.1c11433
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Junction: A Reliable Platform for Monitoring Molecular Physical and Chemical Processes

Abstract: Monitoring and manipulating the physical and chemical behavior of single molecules is an important development direction of molecular electronics that aids in understanding the molecular world at the single-molecule level. The electrical detection platform based on single-molecule junctions can monitor physical and chemical processes at the singlemolecule level with a high temporal resolution, stability, and signal-to-noise ratio. Recently, the combination of singlemolecule junctions with different multimodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 178 publications
3
79
0
Order By: Relevance
“…[8][9][10][11][12] Meanwhile, it is also a powerful tool for exploring quantum transport and novel physical phenomena. [13][14][15][16][17][18][19] Therefore, single-molecule FETs have been widely studied. Single-molecule FETs are generally constructed by sandwiching a molecule between two electrodes, and the charge transport through the single molecule is regulated by the gate electric field.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Meanwhile, it is also a powerful tool for exploring quantum transport and novel physical phenomena. [13][14][15][16][17][18][19] Therefore, single-molecule FETs have been widely studied. Single-molecule FETs are generally constructed by sandwiching a molecule between two electrodes, and the charge transport through the single molecule is regulated by the gate electric field.…”
Section: Introductionmentioning
confidence: 99%
“…The graphene–molecule–graphene SMJ (GMG-SMJ) is known for its high stability, making it suitable for reaction kinetics and dynamic study. 47 For example, the Guo group's development of the GMG-SMJ opened a route towards understanding the dynamics of chemical reactions at the single-molecule level. Their recent work investigated the nucleophilic addition of NH 2 OH to a carbonyl and reported strong solvent-dependent reversibility judging from the stable and sensitive real-time two steps oscillation of the current signals.…”
Section: Driving and Monitoring Chemical Reactionsmentioning
confidence: 99%
“…SMJ not only helps chemists to independently separate the role of each species in electrical conductance, but it is also a formidable tool for understanding the non-covalent reaction mechanism between the host and the guest complexes. 47 The factors to consider for host-guest interactions include conductance, cavity size, linker groups, macrocycle complex/host molecule design, and affinity. 46 There are three main experimental routes to differentiating the specific role of host complexes from the guest molecules in This journal is © The Royal Society of Chemistry 2022 electrical conductance.…”
Section: Hosting-guest Interactionsmentioning
confidence: 99%
“…Several progress reviews in the field of molecular electronics have been reported in terms of device platform, yield, and electrical functionalities. [27][28][29][97][98][99][100][101][102][103][104] For example, Xiang et al provided an overview of molecular junctions at the level of the device platform and charge transport phenomena. [27] Various molecular junction platforms and theoretical simulations were described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Xie et al presented various single molecular junction platforms for monitoring and manipulating the physical and chemical behavior of molecular components. [104] They presented a summary of various dynamic investigations conducted at single-molecular scale and discussed the open issues in this field. All of these reviews, however, have mainly addressed the traditional molecular junction structures (in this review, we refer to them as molecular homojunction systems) based on the metal-molecule-metal junction type first proposed by Aviram and Ratner in 1974.…”
Section: Introductionmentioning
confidence: 99%